Physicochemical, radical scavenging activity and sensory properties of a soft cheese fortified with Arbutus unedo L. extract. (June 2020) - Masmoudi, Manel; Ammar, Imène; Ghribi, Hager; Attia, Hamadi
Abstract: Arbutus unedo L. fruit is known for its high phenolic content, dietary fibers, and antioxidant capacity. This study evaluated the effect of adding A. unedo fruit extract obtained using a water decoction on the physicochemical, DPPH-scavenging activity, textural and sensory properties of a soft "Sardaigne" cheese. Total phenolic content recovered using aqueous extraction was 23.4 mg GAE/g extract. The characterization of the extract using LC-MS showed that quinic acid and catechin were the main phenolic compounds. The scavenging activity of the fruit extract was evaluated using the DPPH radical scavenging assay. The IC50 value was ~0.31 mg/ml. The cheese, fortified with A. unedo extract, showed an increase in crude protein and firmness. Incorporation of the extract at 0.3 g/l increased the cheese yield, improved its DPPH scavenging activity after 5 days of storage and did not alter its color and sensory properties. These results suggested that addition of A. unedo extract to soft cheese at 0.3 g/l might be a functional ingredient with potential health benefits and good properties. Highlights: Phenolic compounds of a Tunisian Arbutus unedo L. extract were characterized. Arbutus extract was used as a functional ingredient in soft cheese. Arbutus decoction extracts improved DPPH scavenging activity of cheeses. Addition of the lowest dose of decoction extract increased the cheese yield. Cheeses fortified with decoction had acceptable textural and sensory properties.